Identification of genetic modifiers of behavioral phenotypes in serotonin transporter knockout rats - Nijman Isaäc J; Homberg Judith; Kuijpers Sylvia; Cuppen Edwin (BMC Genetics, 2010)
Abstract Background Genetic variation in the regulatory region of the human serotonin transporter gene (SLC6A4) has been shown to affect brain functionality and personality. However, large heterogeneity in its biological effects is observed, which is at least partially due to genetic modifiers. To gain insight into serotonin transporter (SERT)-specific genetic modifiers, we studied an intercross between the Wistar SERT-/- rat and the behaviorally and genetically divergent Brown Norway rat, and performed a QTL analysis. Results In a cohort of >150 intercross SERT-/- and control (SERT+/+) rats we characterized 12 traits that were previously associated with SERT deficiency, including activity, exploratory pattern, cocaine-induced locomotor activity, and abdominal and subcutaneous fat. Using 325 genetic markers, 10 SERT-/--specific quantitative trait loci (QTLs) for parameters related to activity and exploratory pattern (Chr.1,9,11,14), and cocaine-induced anxiety and locomotor activity (Chr.5,8) were identified. No significant QTLs were found for fat parameters. Using in silico approaches we explored potential causal genes within modifier QTL regions and found interesting candidates, amongst others, the 5-HT1D receptor (Chr. 5), dopamine D2 receptor (Chr. 8), cannabinoid receptor 2 (Chr. 5), and genes involved in fetal development and plasticity (across chromosomes). Conclusions We anticipate that the SERT-/--specific QTLs may lead to the identification of new modulators of serotonergic signaling, which may be targets for pharmacogenetic and therapeutic approaches.